Homochiral one-dimensional ABX3 lead halide perovskites with high-Tc quadratic nonlinear optical and dielectric switchings. (10th May 2021) - Peng, Hang; Liu, Yu-Hua; Huang, Xue-Qin; Liu, Qin; Yu, Zi-Hong; Wang, Zhong-Xia; Liao, Wei-Qiang
Abstract : Two new homochiral 1D ABX3 -type lead-halide perovskites exhibit dual dielectric and quadratic nonlinear optical switchings at high temperatures. Abstract : Chiral organic–inorganic hybrid lead-halide perovskites have attracted increasing attention for their wide application prospects in chiroptoelectronics, such as circularly polarized light (CPL) photodetectors and LEDs, nonvolatile memories, and spintronics. Herein, we have successfully synthesized two new homochiral lead-halide perovskites [ R -MP]PbX3 ( R -MP = R -2-methylpiperidinium, X = Br and I). They possess one-dimensional (1D) ABX3 perovskite structures consisting of homochiral [ R -MP] + cations and infinite [PbX3 ] − chains along the a -axis, which are assembled by the highly distorted face-sharing PbX6 octahedra. [ R -MP]PbBr3 and [ R -MP]PbI3 exhibit high-temperature phase transition at around 460.7 K and 409.3 K, respectively, accompanied by evident dielectric switching characteristics. T c for both are higher than that of most reported chiral phase transition materials. Besides, the homochiral [ R -MP]PbX3 are SHG (second harmonic generation) active and demonstrate excellent SHG switchings between the 'SHG-ON' and the 'SHG-OFF' states. The SHG 'ON/OFF' contrast of [ R -MP]PbBr3 and [ R -MP]PbI3 is as high as 43 and 46, respectively, which are among the highest ones in molecular-based quadratic nonlinear optical switches. This study highlights the functional properties of chiral lead-halide perovskites for potential dual dielectric and nonlinear optical switching materials.